1995
DOI: 10.2136/sssaj1995.03615995005900050013x
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Assessment of Long‐Term Phosphate Desorption from Soils

Abstract: A new method was developed to study P desorption kinetics. This new technique uses dialysis membrane tubes, filled with hydrous ferric oxide (ferrihydrite) acting as an “infinite” P sink. This system is mechanically stable for very long reaction periods, provided that a microbial inhibitor, e.g., chloroform, is added to the soil suspension to prevent hydrolysis of the membrane. The pH of the soil solution during desorption remains almost constant. After the desired time of contact between soil suspension and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 0 publications
3
57
2
Order By: Relevance
“…Long-term P desorption study was done on the selected samples using dialysis membrane tubes filled with hydrous ferric oxides as described by Freese et al (1995). The dialysis membrane tubes filled with hydrous ferric oxide were placed in a 200-ml polyethylene bottle containing 1 g of soil and 80 mL of 2 mM calcium chloride (CaCl 2 ) and 0.3 mM KCl solution.…”
Section: Long-term Phosphate Desorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term P desorption study was done on the selected samples using dialysis membrane tubes filled with hydrous ferric oxides as described by Freese et al (1995). The dialysis membrane tubes filled with hydrous ferric oxide were placed in a 200-ml polyethylene bottle containing 1 g of soil and 80 mL of 2 mM calcium chloride (CaCl 2 ) and 0.3 mM KCl solution.…”
Section: Long-term Phosphate Desorption Experimentsmentioning
confidence: 99%
“…where SP is solid phase P, P sol is P in solution, P HFO is P adsorbed by HFO, k T is the rate constant of P transport through the membrane (0.09 ¡ 0.01h 21 ; Freese et al 1995), and k R is the rate constant of P release (de Jager and Claassens 2005). The presence of two pools is assumed: the pools with the fast release kinetics, pool A (SP A ), and the pool with the slow release kinetics, pool B (SP B ).…”
Section: Theorymentioning
confidence: 99%
“…First, some P is removed from exchange with solution by burial within the surface precipitate and thus is no longer part of the equilibrium process. It is clear from isotopic exchange studies, as well as from desorption studies, that much of the P on the goethite surface is not in rapid equilibrium with the solution P (8,12,15,16). Precipitation may be contributing to that lack of exchange.…”
Section: Zeta Potential Measurement Of Goethite At Different Ph Valuementioning
confidence: 99%
“…Van der Zee et al (1987) proposed to use Fe oxide-impregnated filter paper (Pi-paper) which was found to sorb P selectively and strongly. For the assessment of long-term P desorption kinetics, dialysis membrane tubes filled with hydrous ferric oxide have been proposed by Freese et al (1995).…”
Section: Introductionmentioning
confidence: 99%